MELPHALAN-INDUCED CYTOTOXICITY IN THE BONE MARROW OF RATS BY FLOW CYTOMETRY MEASUREMENTS - Gerashchenko, B I.; Todor, I. M.; Shevchuk, O. O.; Nikolaev, V. G. (International Journal of Medicine and Medical Research, 2019)
Background. Bone marrow (BM) that contains hematopoietic cells of various lineages is a sensitive target for a number of cytotoxic agents including chemotherapy drugs. Objective. Flow cytometry (FCM) was chosen to test cytotoxicity in BM of rats, that received melphalan either intravenously (i.v.) or intraperitoneally (i.p.). Methods. One group of rats received melphalan i.v. (3 mg/kg) followed by the BM examination on the 3rd and 7th day after drug administration, whereas another group of animals received this drug i.p. in total doses of 9 and 15 mg/kg followed by the BM examination on the next day after the 3rd and 5th injection of the drug. BM cells were stained with acridine orange and analyzed by FCM. Cytotoxicity was assessed by determining the percentage of total nucleated cells (TNC%) among the whole BM cell population and by determining the percentage of polychromatic erythrocytes (PCE%) among the whole population of enucleated erythrocytes. Results. Regardless of the dose and regimen of melphalan administration, either i.v. or i.p. administered drug caused a significant reduction of TNC%. On the average, the i.p. administered drug resulted in about 2.0-fold decrease of TNC% (P<0.05), while the i.v. administered drug resulted in about 1.3-fold decrease of TNC% (P<0.05). As for enucleated erythrocytes, the i.p. administered drug resulted in about 1.4-fold decrease of PCE% (P<0.05), whereas the i.v. administered drug did not cause any changes in the PCE%. Conclusions. Under these experimental conditions, i.p. administrated melphalan is considerably more cytotoxic than i.v. administered melphalan. This cytotoxic effect is preferentially due to impaired erythropoiesis.